2014
DOI: 10.1681/asn.2013050565
|View full text |Cite
|
Sign up to set email alerts
|

Renal-Retinal Ciliopathy Gene Sdccag8 Regulates DNA Damage Response Signaling

Abstract: Nephronophthisis-related ciliopathies (NPHP-RCs) are developmental and degenerative kidney diseases that are frequently associated with extrarenal pathologies such as retinal degeneration, obesity, and intellectual disability. We recently identified mutations in a gene encoding the centrosomal protein SDCCAG8 as causing NPHP type 10 in humans. To study the role of Sdccag8 in disease pathogenesis, we generated a Sdccag8 gene-trap mouse line. Homozygous Sdccag8 gt/gt mice lacked the wild-type Sdccag8 transcript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 44 publications
4
74
1
3
Order By: Relevance
“…Because the effects of CDK1/2 inhibition on the cell cycle might bias our These insights into the pathogenesis of CEP290 loss are reminiscent of the molecular functions of another ciliopathy protein, NEK8 (16). Furthermore, increased DNA damage signaling was seen in CEP164-, ZNF423-, and SDCCAG8-associated NPHP (14,15) and hints at a general disease mechanism. It is interesting to note that CEP290 loss affects centriole duplication outside the nucleus.…”
Section: B Levels Were Higher In Cep290mentioning
confidence: 98%
See 1 more Smart Citation
“…Because the effects of CDK1/2 inhibition on the cell cycle might bias our These insights into the pathogenesis of CEP290 loss are reminiscent of the molecular functions of another ciliopathy protein, NEK8 (16). Furthermore, increased DNA damage signaling was seen in CEP164-, ZNF423-, and SDCCAG8-associated NPHP (14,15) and hints at a general disease mechanism. It is interesting to note that CEP290 loss affects centriole duplication outside the nucleus.…”
Section: B Levels Were Higher In Cep290mentioning
confidence: 98%
“…CEP290 also localizes to the nucleus, although its function there is entirely unknown (1). One possibility is that CEP290 acts in a manner similar that of the other ciliary proteins mutated in renal ciliopathies (CEP164, ZNF423, SDCCAG8, NEK8), which have been associated with enhanced DDR signaling (14)(15)(16). A single study examining the events leading to DNA damage in this setting recently established a role for NEK8 in the ATR-regulated replication stress response and in the regulation S-phase cyclin-dependent kinase (CDK) activity (16).…”
Section: Introductionmentioning
confidence: 99%
“…Both polycystin 1 and polycystin 2 are functionally expressed in B-lymphoblastoid cells [128, 129], while polycystin 1 is also expressed in peripheral blood lymphocytes [130]. Interestingly, three studies of renal ciliopathies have shown that the initiating mutations involve genes linked to control of DNA damage response signalling, although whether this function or alternative functions of the genes in question are essential for cyst formation is not yet clear [131133]. …”
Section: Adpkd and The Hallmarks Of Cancermentioning
confidence: 99%
“…6-9 Interestingly, recent evidence has shown that several ciliary proteins are unexpectedly related to the regulation of cellular response to DNA damage and DNA repair. 10-12 The kinesin Kif3a is among the many proteins necessary for the building of primary cilia, and kidney-specific inactivation of Kif3a in mice results in loss of cilia and rapid cyst formation in the kidneys. 13 On the contrary, loss of function of the gene GLIS2/NPHP7 , a repressor of Hh signaling, 13 causes a NPHP-like phenotype in humans and mice, characterized by progressive kidney atrophy, interstitial inflammatory infiltration, and fibrosis.…”
mentioning
confidence: 99%